Five Years Outpatients Antibiotics Consumption at Public Tertiary Hospital in Bengkulu According to Access, Watch and Reserve Classification - Apriyanti, Yusna Fadliyyah; Saepudin; Siti Maisharah S. Gadzi (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Access, Watch, and Reserve (AWaRe) antibiotics classification was released in 2019 by the World Health Organization (WHO) to enhance antimicrobial stewardship programs in all healthcare facilities. As a result, WHO advises global action to increase the availability of antibiotics from the Access group by more than 60%.Objective: to determine antibiotics consumption for outpatients at a public tertiary hospital in Bengkulu, Sumatera-Indonesia, from 2018 to 2022, focusing on antibiotics from Access class according to the AWaRe classification from WHO and Ministry of Health Republic of Indonesia (MoHRI). Methods: This is a cross-sectional survey analyzing aggregate data on antibiotics use for outpatients at the hospital during the study period. Data on antibiotics were collected from the hospital pharmacy department, while data on patient visits were collected from the medical records department.  The quantity of antibiotics used was calculated using the ATC/DDD method and expressed in DDD/1000 patient-day (PD), which was then converted into a percentage. Results: During the study period, 50-60% and 65-73% out of 14-19 antibiotic agents are from Access class according to WHO and MoHRI AWaRe classification, respectively. Quantitatively, according to the WHO and MoHRI AWaRe classification, the consumption of antibiotics from the Access class was 25-50% and 33-71% of total consumption, respectively. In addition, the segment of drug utilization 90% (DU90%) of antibiotics was dominated by antibiotics from Watch class. Conclusion: The hospital has not yet met the WHO target for antibiotic consumption from the Access class, highlighting the need for some effective efforts from Watch class to limit the usage of antibiotics.